Influences on New Jersey public library budget requests. Issue 2 (8th August 2016) - Beckett, Edith K.
Abstract : Purpose: This research study aims to examine influences on the public library funding decision from the perspectives of New Jersey mayors and public library directors. Design/methodology/approach: Content analysis was used to explore statements of 84 public library directors and 45 mayors about what was most/least effective in a recent library budget request. Findings: Although they may differ on the relative importance of a specific concept, the public library directors and mayors in this study have high levels of agreement about what information is important in the budget decision process. Research limitations/implications: The primary limitations of the findings of this study stem from the reliability of self-reported data and the low response rates. While the researcher believes that the findings and conclusions are valid for the survey respondents, it is less certain that they are valid for all public libraries in New Jersey, and it is not recommended that the conclusions be extended to public libraries outside of the state which differ in state mandates and other circumstances. Practical implications: Understanding more about the factors that can influence library funding decisions provides insight into the very complex public library funding process and may help public library directors and mayors engage in mutually satisfactory budget negotiations. Originality/value: This study contributes to the Library and Information Science research literature on library budgets by examining influences on the public library funding decision, specifically adding the perspectives of mayors and public library directors on a recent budget cycle.